Comparative Study: Pakistani Media Laws vs. International Free Speech Norms (UN, EU, US): https://doi.org/10.55966/assaj.2025.4.1.076 - Irtaza Hassan; Zeesham Zafar; Nimra Zafar (`, 2025)
The freedom of press and independence of the media are the landmark components of the democratic world, but their construction and application differ greatly in different jurisdictions. In this study, the researcher undertook comparison of media laws in Pakistan to that of the international norms of free speech in terms of norms that were set at the United Nations, the European Union as well as the United States. Though Article 19 of the Constitution of Pakistan supposedly gives citizens freedom of speech, there are numerous and broad restrictions imposed by numerous legislations, including the Pakistan Electronic Media Regulatory Authority (PEMRA) Ordinance, the Prevention of Electronic Crimes Act (PECA) 2016, and others, as well as sedition and defamation laws. Such tools have created a situation of widespread censorship, monitoring and closing down of expression of alternate opinion particularly in the name of religious security or national security or in the name of maintenance of order. In contrast, the international standards, especially the ones in the Universal Declaration of Human Rights (UDHR) and the International Covenant on Civil and Political Rights (ICCPR) adhere to proportionality and necessity in restricting free speech. Europe European norms, especially in the European Convention on Human Rights (ECHR) and jurisprudence of the European Court of Human Rights (ECtHR), have envisaged strong criteria of acceptable speech restrictions, which balanced societal interests with individual rights. The same can be said about the United States, whose understanding of the free speech under the First Amendment implies a nearly absolute principle according to which prior restraint and content-based limitations are put to the highest standard of examinations. This paper determines the gaps of the law, institutional and normative between Pakistani regulations of media and the international. It points to the unclarity of the legislative drafting, the excess in use of executive authority and the absence of judicial independence, which are systematic factors that lead to media freedom violations in Pakistan. It further talks about the jurisprudential difference as Pakistani courts have been found to be deferential to state power whereas international courts have been more focused on rendering rights-oriented meanings. By using comparisons of cases and analysis of the law in doctrine, the paper highlights the significance of harmonizing domestic legislations with the international lines so that democracy values are enhanced, hence guarding the reputation of Pakistan as far as human rights are concerned, internationally. The paper finishes with the recommendation of structural reform like reconstitution of PEMRA as an independent institution, repealing or amending overbroad provisions in the statutes and initiative involvement of UN treaty bodies. The reforms would be fundamental in inculcating a media environment that constitutes accountability, pluralism and citizen engagement. Finally, the study is also aimed at contributing to the on-going debates regarding the importance of legal reform, media independence and the tendency of Pakistan to follow its agreements on the international level.